Detection of Antibody Titers Against New-Castle Disease Virus (ND) and Monocyte Profile in Free-Range Chickens (Gallus domesticus) at a Farm in Permata Village, Tilongkabila Sub-district, Bone Bolango District - Suaiba, Zachrianty; Djuna, Lamondo; Wirnangsi Din, Uno; Yuliana , Retnowati; Margaretha , Solang; Kristina Dwi , Wulandari (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2024)
Abstract: This study aims to determine the presence of Newcastle Disease (ND) virus antibody titers and the percentage of monocyte cells in native chickens (Gallus domesticus) at a farm in Permata Village, Tilongkabila Subdistrict, Bone Bolango Regency. The method used in this research is qualitative descriptive. Antibody titer data were obtained from the results of the HI (Haemagglutination Inhibition) test, while the percentage of monocyte cells was determined using 10% Giemsa staining with parallel track counting.The results showed that out of 50 samples, 10 samples tested positive for antibody titers (20%), while 40 samples tested negative (80%). For positive antibody titer samples, leukocyte count totaled 3,310, with 250 monocytes, yielding a percentage of 7.55%. For negative samples, leukocyte count totaled 10,560, with 360 monocytes, resulting in a percentage of 3.20%, which falls within the normal range of monocyte cell values.